Progress towards xenogenic tolerance. Issue 5 (October 2020) - Duggan, Erin M.; Griesemer, Adam
Abstract : Purpose of review: To describe the most recent progress towards tolerance in xenotransplantation. Recent findings: Mixed chimerism and thymic transplantation have been used to promote tolerance in xenotransplantation models. Intra-bone bone marrow transplantation is a recent advance for mixed chimerism, which promotes longer lasting chimerism and early graft function of subsequent organ transplantation. The hybrid thymus, an advancement to the vascularized thymokidney and vascularized thymic lobe, is being developed to allow for both donor and recipient T-cell selection in the chimeric thymus, encouraging tolerance to self and donor while maintaining appropriate immune function. Regulatory T cells show promise to promote tolerance by suppressing effector T cells and by supporting mixed chimerism. Monoclonal antibodies such as anti-CD2 may promote tolerance through suppression of CD2+ effector and memory T cells whereas Tregs, which express lower numbers of CD2, are relatively spared and might be used to promote tolerance. Summary: These findings contribute major advances to tolerance in xenotransplantation. A combination of many of these mechanisms will likely be needed to have long-term tolerance maintained without the use of immunosuppression.